Promoting higher levels of immunity from colostrum among calves on organic dairy farms - Munashe Chigerwe; Hannah M. Laurence; Maire C. Rayburn; Betsy M. Karle (California Agriculture)
Abstract: Colostrum feeding provides immunoglobulins, in a process called transfer of passive immunity, which is critical for dairy calf health and welfare. However, failure of transfer of passive immunity (FTPI) occurs in about 12% of calves nationwide. This study compares the prevalence of FTPI between calves raised on organic and conventional dairy farms, describes the colostral management practices on organic dairy farms in California, and recommends improvements. We compared serum immunoglobulin G (IgG) concentrations between calves raised on organic and conventional dairies and found that the odds of FTPI in calves raised in organic dairies were 2.5 times greater than in calves raised in conventional dairies. Focusing on varied practices in organic dairies, FTPI was 2.9 times more likely in calves fed less than 4 liters of colostrum within the first 24 hours, compared to calves fed more than that amount. We also found that organic dairy producers did not routinely monitor colostral IgG concentrations and passive immunity status. We recommend that organic dairy farmers adopt these practices to decrease the prevalence of FTPI in calves.